(untitled) - Minasi, Mark (Indianapolis, IN, 2007)
Get an early start on Windows Vista security and the technology shifts you'll need to know as a systems administrator. From leading Windows expert Mark Minasi comes this "just-in-time" book to get you there. This targeted, hands-on guide takes a rapid-fire approach to the biggest security changes and how they'll affect business as usual for those who must integrate and provide technical support for Windows Vista. You'll find practical instruction, tips, workarounds, and much more. Work through a slew of Vista surprises, such as logging on as Administrator and how to re-enable Run. Discover how virtualization works--and where it doesn't. Find out why you can no longer delete files in System32, even though you are an Administrator
Keywords: Computer security,An ninh máy tính